2021
DOI: 10.1007/s44197-021-00018-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards COVID-19 Vaccine: A Survey of Health Care Workers in Oman

Abstract: Coronavirus Disease 2019 (COVID-19) vaccine hesitancy among health care workers (HCWs) is widely reported. Here we report on the prevalence of vaccine hesitancy and the factors associated with it in a sample of non-vaccinated HCWs. Data from 433 not vaccinated medical and non-medical HCWs from various health care facilities after the introduction of COVID-19 vaccination in Oman were analyzed. Most of the participants were nurses (41.5%) followed by physicians (37.5%) and non-medical HCWs (21%). Forty percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Consistent with previous findings [2][3][4][5][6][7][8], female gender, younger age, lower education and socioeconomic status, and living in rural regions predicted vaccine hesitancy. Importantly, these particular groups have also been identified as those who have been affected the most by the pandemic with regards to their mental health in Austria [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous findings [2][3][4][5][6][7][8], female gender, younger age, lower education and socioeconomic status, and living in rural regions predicted vaccine hesitancy. Importantly, these particular groups have also been identified as those who have been affected the most by the pandemic with regards to their mental health in Austria [18].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there is also conflicting evidence about some identified predictors. For example, in studies conducted in Australia, the USA, Austria, and Oman, male gender was associated with intentions to get vaccinated against COVID-19 [ 4 6 , 8 ], whereas in a sample of 1658 respondents from the general population in Bangladesh, men had more vaccine hesitancy than women [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Safety and efficacy concerns have been described as the most common reasons for VH among general population and HCW within different territories. They have been reported as main concerns in studies in London [30], Oman [31], Hong Kong [32], Ethiopia [33], Istanbul [34], and Switzerland [35] among others. They have also been mentioned in different systematic reviews during the first year of pandemic, such as Al-Amer et al [20], who targeted both as the main concern to address, especially in nurses, and Li et al [22], who reported them as main barriers, together with distrust of the government.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference as regard age, gender or working with COVID-19 patients in our cohort. In previous studies, it was observed that males and physicians were more accepting of vaccinations than females and nurses [40] [24] [41]. Because of this, physicians play a signi cant part in increasing public acceptability of the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as more information about the safety and e cacy of COVID-19 vaccines becomes available, individuals may have different attitudes towards vaccination. 182 (40) 132 (29) 86 (18.9) 4 (0.9)…”
Section: Discussionmentioning
confidence: 99%